GAMBARAN KONSEP DIRI SISWA KELAS XI IPA DI SMAN 4 CIMAHI - Tia Ramadhanti; Ecep Supriatna; Devy Sekar Ayu Ningrum (IKIP Siliwangi, 2023)
This research was conducted to find out the description of self-concept in class XI science students at SMAN 4 Cimahi. According to Burns, (1993) self-concept is the main part that exists in each individual because it is considered important as an attitude that tends to influence individual behavior. Quantitative approach with descriptive method is the method used in this research. The research sample was taken using a purposive sampling technique, as well as a measuring instrument in the form of a questionnaire derived from the self-concept theory by Burns (1993) which amounted to 12 statements with a sample of 32 students with male and female gender. The results showed that the frequency of 28 students (73%) with positive self-concept, namely, 7 male students and 16 female students, while the frequency of 9 students (28%) with negative self-concept, namely, 2 male students and 7 students. woman.Keywords: self-concept, Student